The Role of Parents in Forming Children's Mental Health - Syam, Andi Fatmawati; Ichsan, Nursyamsi; Nasir, Citra (Cendekiawan Indonesia Timur, 2022)
This study employs normative legal research to explore the intersection between psychiatry and legal investigations, focusing on the role of psychiatrists in contributing information to investigative processes. Through a descriptive methodology and qualitative analysis of secondary data, including primary, secondary, and tertiary legal materials, this research delves into the legal and ethical considerations that psychiatrists face. It highlights the complex dynamics of confidentiality, consent, and the therapeutic relationship within the legal context. The study further examines the broader implications of mental health, particularly among children and adolescents, emphasizing the significance of a nurturing environment and the pivotal role of the family in fostering mental well-being. It underscores the need for comprehensive mental health education and the development of preventive measures to enhance the resilience of the youth against mental health challenges.